Guarantee Of Worker Rights During The Covid 19 Pandemic - Agustanti, Rosalia Dika; Wahyuningsih, Yuliana Yuli; Satino, Satino (Jambura Law Review, 2021)
This research discusses the rights of workers / laborers during the COVID-19 pandemic and what if the employers do not meet these rights. Problem which is more in-depth about the employment that emerged during this pandemic, namely the occurrence of massive layoffs. The research was conducted using the Normative Juridical method. By applying the Statute Approach, Conceptual Approach, and Case Approach, the results show that employers have not been able to fulfill workers / labor rights during the COVID-19 pandemic. There are companies that have not implemented the clean lifestyle and occupational health standards K3 protection such as masks, hand sanitizer and personal protective equipment. Prevention and handling policies are still not optimal, the principle of maintaining social distancing has not been implemented optimally, there are still many workers who are jostling for work when they come to work, not to mention during the trip to work in public transportation.  This situation makes them vulnerable to infection. However, they still have to go to work because of the risk of losing their income. Efforts that can be made if wages are not paid are to take the route or methods as regulated in Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. The basis of a dispute between a worker/ laborer and an entrepreneur is a dispute over rights.